Comparative Genomics Provide Insights into Evolution of Trichoderma Nutrition Style - Xie, Bin-Bin; Qin, Qi-Long; Shi, Mei; Chen, Lei-Lei; Shu, Yan-Li; Luo, Yan; Wang, Xiao-Wei; Rong, Jin-Cheng; Gong, Zhi-Ting; Li, Dan; Sun, Cai-Yun; Liu, Gui-Ming; et al. (Genome biology and evolution, 2014)
Saprotrophy on plant biomass is a recently developed nutrition strategy for Trichoderma. However, the physiology and evolution of this new nutrition strategy is still elusive. We report the deep sequencing and analysis of the genome of Trichoderma longibrachiatum, an efficient cellulase producer. The 31.7-Mb genome, smallest among the sequenced Trichoderma species, encodes fewer nutrition-related genes than saprotrophic T. reesei (Tr), including glycoside hydrolases and nonribosomal peptide synthetase-polyketide synthase. Homology and phylogenetic analyses suggest that a large number of nutrition-related genes, including GH18 chitinases, β-1,3/1,6-glucanases, cellulolytic enzymes, and hemicellulolytic enzymes, were lost in the common ancestor of T. longibrachiatum (Tl) and Tr. dN/dS (ω) calculation indicates that all the nutrition-related genes analyzed are under purifying selection. Cellulolytic enzymes, the key enzymes for saprotrophy on plant biomass, are under stronger purifying selection pressure in Tl and Tr than in mycoparasitic species, suggesting that development of the nutrition strategy of saprotrophy on plant biomass has increased the selection pressure. In addition, aspartic proteases, serine proteases, and metalloproteases are subject to stronger purifying selection pressure in Tl and Tr, suggesting that these enzymes may also play important roles in the nutrition. This study provides insights into the physiology and evolution of the nutrition strategy of Trichoderma.